National Crime Victimization Survey: School Crime Supplement, 1999 ([Verlag nicht ermittelbar], 2001)
This supplement to the National Crime Victimization Survey (formerly the National Crime Surveys) was designed to collect data on crime victimization in schools in the United States. Student respondents were asked a series of questions to determine their school attendance in the last six months. Other questions concerning schools were posed, including preventive measures employed by schools, students' participation in after-school activities, students' perception of school rules and enforcement of these rules, the presence of weapons, drugs, alcohol, and gangs in school, student bullying, hate-related incidents, and attitudinal questions relating to the fear of victimization at school. Other variables cover general violent crimes, personal larceny crimes, and household crimes and offer information on date, time, and place of crime. Demographic characteristics of household members such as age, sex, race, education, employment, median family income, and marital status are provided.